TRADISI MASUK SUKU PADA ADAT PERKAWINAN MASYARAKAT MELAYU DI DESA SINTONG KECAMATAN TANAH PUTIH KABUPATEN ROKAN HILIR - Agusniyarni, Agusniyarni; Ibrahim, Bedriati; Tugiman, Tugiman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Sintong Village is a village where the majority of the people are Malay tribe besides the Malay tribe, there are also other tribes such as Javanese, Batak, Minang and so on. Although there are many tribes in Sintong, the community still uses Malay cultural customs both in daily life, marriage and other customary events. Communities in Sintong Village recognize the tradition of entering tribes as a series of customary processes that will be traversed by non-Malay people who will carry out inter-tribal marriages by entering a tribe in Sintong Village. The tradition of entering tribes in Sintong Village is still applied in inter-tribal marriages and its implementation is carried out in accordance with the stages of the prevailing customs in Sintong. The ethnic entry tradition is inseparable from the kinship system used by the Melayu Sintong community, the Sintong community kinship system can be seen from the legal form in the marriage system that they apply, where the Sintong community marriage law is of the lineage and is closely related to the Malay tribe used. The purpose of this study was to find out the background of the non-Malay community following the tradition of tribal entry, to find out the entry requirements of the tribe in Sintong Village Tanah Putih District, Rokan Hilir Regency, to find out the procedures for implementing tribal traditions in the marriage customs of Malay communities in Sintong Village and to find out the values contained in the implementation of the tradition of entering tribes in the marriage customs of Malay communities in Sintong Village. The method used in this research is descriptive method using a qualitative approach. The results of this study are that entering tribes as a tradition has long been applied in Sintong, entering the tribal implementation starting from looking for foster parents, meeting the top of the tribe of foster parents, after which new tribal entry is carried out.Key Words: Tradition, Tribal entering, Sintong Malay Community